Misconception of weights, normal forces and Newton third law - Mongan, S W; Mondolang, A H; Poluakan, C (Journal of physics. Conference series, 2020)
Research has been conducted relating to the concept of forces in physics learning. The purpose of this study is to identify student's misconception and difficulties in determining the weight and normal from tail of vector, the weight and the normal direction of vector and Newton third law. The study was conducted in two groups of students. The first group was microteaching class and the second group was students who had studied mechanics. The research method is carried out with two approaches namely qualitative and quantitative. The quantitative method is done by using a test instrument given to participants through the pre-test and post-test stages. While the qualitative method of conducting interviews with participants after the post-test session. The results of the study showed that 55% of students were unable to determine the exact gravity capture point, and 93% of students were unable to describe the exact position of the normal force, and 95% of students answered incorrectly about the concept of action forces similar to the reaction forces. From the interviews, it was revealed that students were still confused by the representation of the vector of force representations and not sure about the drawing vector they made. Physics will be well understood if style concept learning is given on the basis of the philosophy of science correctly. Research recommendations are very important that students understand the concept of forces correctly which is based on the application of appropriate vector concepts.